PENGEMBANGAN BAHAN AJAR IPA TERPADU BERORIENTASI PEMBELAJARAN KONTEKSTUAL TEMA PEMANFAATAN TEKANAN DALAM KEHIDUPAN UNTUK MENINGKATKAN LITERASI SISWA KELAS VIII SMP - Suci Khairani; Asrizal Asrizal; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2017)
Curriculum of 2013 requires science learning is implemented in an integrated teaching. However, the reality in schools shows that the integrated science learning isn’t implemented well yet. The solution of this problem is to  develop an integrated science teaching material which orient contextual learning to improve students’ literacy. The purpose of  research is to determine validity, practicality, and effectiveness of integrated science teaching material. The type of this research is Research and Development (R & D). The object of the research was integrated science teaching material which orient contextual learning. Instruments to collect the data consist of validition sheet, practicality test sheet, and effectiveness test sheet. Techniques of data analysis were descriptive statistics analysis, graph method, and correlation compare mean test. Based on data analysis it can be stated that two of research results. First, integrated science teaching material which orient contextual learning was very valid with an average value of 83.2. Second, implementation of integrated science teaching material which orient contextual learning was practice according teacher and students with average value respectly of 90.0 and 83.5. Besides that, implementation of integrated science teaching material which orient contextual learning was effective to improve the competence of attitudes, knowledge, and skills. Students skills consist of  functional literacy, scientific literacy and visual literacy